Strategi Komunikasi Pemasaran Restoran Rumpis Kitchen dalam Mempertahankan Bisnis Pada Masa Pandemi Covid-19 - Sayu Diah Wismayani; Ni Made Yuliani; ulio lio (UHN IGB Sugriwa Denpasar, 2023)
Covid-19 pandemic affects several aspects generally in economics aspect causing business to close permanently. One business that capable to maintain it business is Rumpis Kitchen restaurant this indeed can’t be separated from their applied marketing communication strategy. Based on that, issues to be studied in this research are: how is the implementation of marketing communication strategy to maintain the business of Rumpis Kitchen restaurant during the pandemic? What are the obstacles of marketing communication strategy in maintaining the business of Rumpis Kitchen restaurant during the pandemic? How is the implication of marketing communication strategy to maintain the business of Rumpis Kitchen restaurant during the Covid- 19 pandemic? The theories used to discuss the problems are: integrated marketing communication theory, communication barrier theory, also dependency theory and media effects. This research apply qualitative method with descriptive approach along with the techniques we use to collecting data are interview, observation, and literature study. In this research we found that: the implementation of marketing communication strategy in the Rumpis Kitchen restaurant is by implementing six elements of integrated marketing communication theory, which are: advertising using Instagram and endorsement, direct marketing through telemarketing and website, sales promotion by giving free products, discount, dan giveaway, personal selling by the employees, interactive marketing by Instagram features, and public relation by community service, publication, and championship competition. The obstacles in implementing marketing communication strategy in Rumpis Kitchen restaurant are environmental barrier and consumer barrier. The implication of implementing marketing communication strategy in Rumpis Kitchen restaurant is because of the changes of consumer by cognitive, affective, and behavioral aspects.